Sistem Pakar Identifikasi Modalitas Belajar Siswa Dengan Implementasi Algoritma C4.5 - Soewono, Rachmawati; Gernowo, Rachmat; Sasongko, Priyo Sidik (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
C4.5 Algorithm is one of the classification technique in machine learning which is used in data mining process by build a decision tree which is represent in the rules. The aims of classification technique in data mining is to recognize the regularity of the pattern and the relation in a huge dataset by historical data collection. Studentsâ€™ modalities measurement which is done by the questionnaire is produce historical data which is potentially to be processed to generate the classification that can be converted in rules. The expert acquisition and the C4.5 algorithm classification rules are used as knowledge base in the expert system. Therefore this research is done to build an expert system of the studentâ€™s modalities identification by implementing C4.5 algorithm that can produce seven categories of modalities classification, they are : visual, auditory, kinesthetic, visual-auditory, visual-kinesthetic, auditory-kinesthetic and visual-auditory-kinesthetic which has good in accuracy. The accuracy of the C4.5 algorithm classification and the expert system testing prediction is 80%. Keywords : Expert system; Decision tree; C4.5 Algorithm; Modalities. Â